Synthesis, crystal structure, luminescent, and gas adsorption properties of a new Zn(II) compound with two different dinuclear [Zn2(COO)3] subunits. Issue 7 (3rd July 2017) - Dong, Yanli; Zhou, Pingping
ABSTRACT: Presented here is a new Zn(II) compound, namely [Zn4 (btec)2 (DMA)3 ]n (1 represents this compound, H4 btec = 1, 2, 4, 5-benzenetetracarboxylic acid, DMA = N, N′-dimethylacetamide). This compound crystallizes in orthorhombic P bca space group with a = 19.053(2) Å, b = 18.8010(6) Å, c = 22.9434(8) Å, α = β = γ = 90°, and Z = 8. Single crystal X-ray diffraction analysis reveals that compound 1 features a three-dimensional (3D) framework based on two different dinuclear [Zn2 (COO)3 ] subunits. In addition, the solid-state luminescent property of 1 and the gas sorption properties of the desolvated 1a were also investigated.